Diabetes and Hypertension Differentially Affect Renal Catecholamines and Renal Reactive Oxygen Species - Watson, Anna M. D.; Gould, Eleanor A. M.; Penfold, Sally A.; Lambert, Gavin W.; Pratama, Putra Riza; Dai, Aozhi; Gray, Stephen P.; Head, Geoffrey A.; Jandeleit-Dahm, Karin A. (Frontiers in Physiology, 2019)
Patients with diabetic hypertensive nephropathy have accelerated disease progression. Diabetes and hypertension have both been associated with changes in renal catecholamines and reactive oxygen species. With a specific focus on renal catecholamines and oxidative stress we examined a combined model of hypertension and diabetes using normotensive BPN/3J and hypertensive BPH/2J Schlager mice. Induction of diabetes (5x 55 mg/kg i.p.) did not change the hypertensive status of BPH/2J mice (telemetric 24hr avg. MAP, non-diabetic 131 ± 2vs. diabetic 129 ± 1, n.s at 9 weeks of study). Diabetes-associated albuminuria was higher in BPH/2J vs. diabetic BPN/3J (1205 +196/-169 versus 496 +67/-59 μg/24hr, p=0.008). HPLC measurement of cortical norepinephrine and dopamine showed significantly greater levels in hypertensive mice whilst diabetes was associated with significantly lower catecholamines levels in both strains. Diabetic BPH/2J retained greater levels than diabetic BPN/3J (diabetic: norepinephrine BPN/3J 40±4, BPH/2J 91±5, p=0.010; dopamine: BPN/3J 2±1; BPH/2J 3±1 ng/mg total protein, p>0.001 after 10 weeks of study). Diabetic BPH/2J showed greater cortical tubular immunostaining for monoamine oxidase A and cortical hydrogen peroxide formation was greater in both diabetic and non-diabetic BPH/2J. While catalase activity was greater in non-diabetic BPH/2J it was significantly lower in diabetic BPH/2J (cytosolic: BPH/2J 127±12 vs. 63±6 nmol/min/ml, p<0.001). We conclude that hypertension-associated increases in renal norepinephrine and dopamine, together with diabetes-associated compromised anti-oxidant systems contribute to increased renal oxidative stress in diabetes and hypertension. Elevations in renal cortical catecholamines and reactive oxygen species have important therapeutic implications for hypertensive diabetic patients.